2010
DOI: 10.1016/j.eurpsy.2009.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of caffeine consumption in psychiatric patients. An Italian study

Abstract: Our study highlights the need that a more accurate attention should be paid to the caffeine use which seems to be strongly, although generically, related to different psychiatric disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 46 publications
3
31
1
Order By: Relevance
“…It appears that not all consumers are aware they are dependent on caffeine, or realize that their fatigue, headache, nausea or other symptoms are related to caffeine withdrawal, instead of an illness [13**]. Several authors recommend increasing awareness among both clinicians and patients about the relationship between caffeine use, health, and psychiatric disorders [19*, 28, 34], and also recommend including caffeine use assessments during psychiatric evaluations [26]. Importantly, the last survey of caffeine use in America was published in 2005 [35] and this information needs updating.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It appears that not all consumers are aware they are dependent on caffeine, or realize that their fatigue, headache, nausea or other symptoms are related to caffeine withdrawal, instead of an illness [13**]. Several authors recommend increasing awareness among both clinicians and patients about the relationship between caffeine use, health, and psychiatric disorders [19*, 28, 34], and also recommend including caffeine use assessments during psychiatric evaluations [26]. Importantly, the last survey of caffeine use in America was published in 2005 [35] and this information needs updating.…”
Section: Resultsmentioning
confidence: 99%
“…While this review provides strong evidence that caffeine can exacerbate anxiety and panic disorder, these studies were caffeine challenges and not representative of the patients’ normal caffeine intake. Patterns of actual caffeine consumption among psychiatric patients have been shown to be similar to matched controls; however, maximum lifetime intake was higher among patients [28]. In addition, the prevalence of caffeine dependence and intoxication was reportedly higher in patients, who endorsed consuming more caffeine than intended, having a desire to cut down, and using caffeine despite harm more often than controls [28].…”
Section: Use Despite Harmmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Studies have examined the prevalence of substance use disorder criteria as applied to caffeine, but the majority were conducted among special populations such as heavy or treatment-seeking caffeine consumers or psychiatric patients, they preceded the proposed DSM-5 criteria, or had relatively small sample sizes. 6,[16][17][18][19][20][21][22][23][24][25][26][27] The only general population examination of DSM-defined caffeine use disorder in the United States surveyed 162 current caffeine consumers in Vermont and found that 30% of caffeine consumers met generic DSM-IV criteria for substance dependence as applied to caffeine. 6 The estimated prevalence was less than 10% when a key-criteria strategy similar to that proposed by DSM-5 was adopted.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation included the Diagnostic Interview Schedule for Children-IV-Youth Version (DISC-IV) and modified DISC-IV questions that assessed caffeine dependence based on DSM-IV substance dependence criteria. Table 5: Prospective epidemiologic studies for caffeine use disorder and the prevalence of the disorder based on DSM-IV criteria [113][114][115][116][117][118][119][120].…”
mentioning
confidence: 99%